Karakteristik Tokoh Protagonis, Antagonis, dan Tritagonis dalam Novel Pulang Karya Leila S. Chudori: Kajian Struktural - Rosalina, Evika; Karim, Maizar; Rahmawati, Rahmawati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the characteristics of the protagonist, antagonist, and tritagonist characters in Pulang by Leila S. Chudori based on physiological, psychological, and sociological aspects through a structural approach. The study employed a qualitative descriptive method using a structural approach. The data consisted of words, phrases, sentences, dialogues, and narrative passages depicting character traits in the novel. Data were collected through library research and note-taking techniques and analyzed through identification, classification, interpretation, and conclusion drawing. The findings indicate that Dimas Suryo, as the protagonist, represents longing, identity loss, and the struggles of political exile; Hananto Prawiro, as the antagonist, represents power, domination, and the influence of political authority on social life; while Lintang Utara, as the tritagonist, represents historical awareness and intergenerational reconciliation. These characterizations are constructed through the integration of physiological, psychological, and sociological dimensions that contribute to the overall narrative structure. The study demonstrates that a structural approach effectively reveals the relationship between characterization and other intrinsic elements of the novel while enriching characterization studies in Indonesian literary scholarship.